2013
DOI: 10.1155/2013/709626
|View full text |Cite
|
Sign up to set email alerts
|

Short Tools to Assess Young Children's Dietary Intake: A Systematic Review Focusing on Application to Dietary Index Research

Abstract: Dietary indices evaluate diet quality, usually based on current dietary guidelines. Indices can therefore contribute to our understanding of early-life obesity-risk dietary behaviours. Yet indices are commonly applied to dietary data collected by onerous methods (e.g., recalls or records). Short dietary assessment instruments are an attractive alternative to collect data from which to derive an index score. A systematic review of studies published before April 2013 was conducted to identify short (≤50 items) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 52 publications
(162 reference statements)
1
33
1
1
Order By: Relevance
“…We assessed correlation for comparability with other studies and also compared methods (validity) and repeated administrations (reproducibility) using cross‐classification and Bland–Altman analysis. The agreement across tertiles between methods in our study (mean 53.9% [range 39%–67%] for correct classification) was higher than studies in infants and toddlers in the systematic review by Bell et al (; average 36–38% correctly classified). However, the proportion of infants grossly misclassified (mean 7%, range 2%–15%) was slightly higher than in the review (3–5%).…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…We assessed correlation for comparability with other studies and also compared methods (validity) and repeated administrations (reproducibility) using cross‐classification and Bland–Altman analysis. The agreement across tertiles between methods in our study (mean 53.9% [range 39%–67%] for correct classification) was higher than studies in infants and toddlers in the systematic review by Bell et al (; average 36–38% correctly classified). However, the proportion of infants grossly misclassified (mean 7%, range 2%–15%) was slightly higher than in the review (3–5%).…”
Section: Discussioncontrasting
confidence: 79%
“…Although the CFFQ overestimated intake of fat, overall, there was a tendency to underestimate nutrient intake, including for carbohydrate, fibre, folate, potassium, thiamin, riboflavin, niacin, and vitamin C. In contrast, other studies in preschool children have generally shown that FFQs overestimate nutrient intake (Andersen et al, ; Bell, Golley, & Magarey, ; Gondolf et al, ; Livingstone & Robson, ; Marriott et al, ; Marriott et al, ; Palacios et al, ; Watson et al, ). These studies varied in methodology, nutrients assessed, reference methods, and timeframes.…”
Section: Discussionmentioning
confidence: 91%
“…Ideally a DAT should be validated in a representative sample of the population in which it will be used [12]. Previous reviews have addressed the validity of DATs in school-aged or pre-school children and discussed the challenges that still remain to improve the quality of dietary information obtained from children and adolescents [4,5,13,14]. Most reviews have focussed on specific aspects of diet, such as fruits and vegetables or energy [15,16]; or have only included tools used in specific types of study, for example intervention studies [6].…”
Section: Introductionmentioning
confidence: 99%
“…As food consumption is a modifiable behaviour, identifying toddlers with poor intakes can assist intervention efforts that aim to improve dietary patterns and reduce negative health consequences . Because of the benefits of short, simple dietary assessment tools, yet lack of such tools for use in young children, a short toddler dietary questionnaire (TDQ) that assesses dietary risk was developed . The 19‐item TDQ assesses ‘core’ (e.g.…”
Section: Introductionmentioning
confidence: 99%